Anatomija človeškega telesa: Compendium topografske anatomije in navodila za vaje - Pejković, Božena (2021)
Anatomy of Human Body: Compendium of Topographic Anatomy and Instructions for Exercises. Compendium of topographic anatomy and instructions for exercises is a textbook manual that enables medical students  together with lectures, seminaries, exercises and studies of supplementary professional literature to repeat their already achieved knowledge in topographic anatomy in a short time, it informs the students with general regulations and most common procedures of anatomical macrodissection.1st reprint of first edition: 9. 8. 20212nd reprint of first edition: 24. 6. 2024
Keywords: human anatomy; topography; compendium; macrodissection; instructions